Complex Telecommunication and Auto-Technical Expertise - M. H. Shcherbakovskyi; V. A. Korshenko (Bulletin of Kharkiv National University of Internal Affairs)
The presence of more electronics onboard vehicle systems transforms them from simple means of transportation to powerful telecommunication devices, capable of receiving and transmitting information in various ways, analyzing the obtained information and performing various actions on the basis of the received data, starting from managing the work of individual transport units up to self-driving motion. The available techniques of auto-technical expertise are not able to answer all the questions that may be raised in criminal and administrative cases, as well as in the consideration of civil claims for damages’ compensation and damages in road accidents involving modern vehicles. The analysis of forensic practice allows to specify directions of increasing the efficiency of research on establishing the circumstances of road accidents: improvement of the methods for carrying out forensic auto-technical expertise, improvement of qualification and professional skills of forensic motor technician’s experts, carrying out of complex telecommunication and auto-technical expertise. The main task of an expert in the field of telecommunications during the conduction of complex telecommunication and auto-technical expertise is to extract the necessary information from certain telecommunication devices installed in the vehicle, which is under study, to determine the methods for their installation and connection and communication channels. The introduction of modern technologies for diagnosing electronic systems of vehicles into modern practice is a prerequisite for improving the efficiency of forensic auto-technical expertise, and the most effective use of these technologies is achieved by engaging in research in the format of carrying out complex telecommunication and auto-technical expert examinations in the field of telecommunications.